The verbless sentence of Biblical Hebrew: a grammatical and a text-linguistic reading - Condrea, Vasile A. (Liber annuus, 2021)
Along with the verbal sentence (where a subject accomplishes an action), Lucien Tesnière argues that there is an attributive sentence - where a subject receives an attribute. Two attributive relations exist: (1) sentences with ‘to be’, and (2) verbless sentences. Focusing on the verbless sentence of Biblical Hebrew, this paper explains that the absence of the verb has a linguistic consequence: following Harald Weinrich, the verbless sentence is dependent on its ‘linguistic context’. That is, its syntactic value is provided by its syntactic VSO or SVO ‘head’. This paper begins with a discussion on methodology drawing on Tesnière and Weinrich, and proceeds with a grammatical and a text-linguistic analysis of the verbless sentence as found in the indirect speech of 1Samuel. With regard to the claim of Zewi 1994 (‘the subject and predicate of the nominal sentence are indistinguishable from … "theme" and "rheme" ’), this paper explains that her position is methodologically unconvincing and invalidated by several examples.